MYCOBACTERIA AND OTHER ACID FAST ORGANISMS ASSOCIATED WITH PULMONARY DISEASE IN JOS, NIGERIA PULMONARY DISEASE AND ACID FAST ORGANISMS - AE, Ani; B, Diarra; UR, Dahle; C, Lekuk; F, Yetunde; AM, Somboro; Tounkara, Anatole; J, Idoko (Institute of Topical Disease Universitas Airlangga, 2012)
Objective: Acid fast bacilli (AFB) for sputum smear microscopy is the affordable method used for prompt diagnosis of tuberculosis in Nigeria despite its lack of specificity and limited sensitivity. The study aims to identify Mycobacterium tuberculosis and other acid fast organisms isolated from sputum of of HIV positive adult patients with pulmonary disease in Jos, Nigeria. Methods: Acid fast organisms isolated from 80 AFB positive sputa of HIV positive adult patients suspected for tuberculosis in Jos, Nigeria were identified for members of M. tuberculosis Complex (M tuberculosis, M bovis, M africanum, M canetti M. microti and M. caprae) by use of spoligootyping, Multiplex Gen Probe, Hain genotype assay and gene sequencing for spoligotype negative isolates. Results: Seven different spoligotypes of M. tuberculosis complex were identified from 70/80 (87.5%) total number of isolates. M. kansasii (1), M. dulvalii (1) Nocardia species (1) and Tsukamurella species (2) were detected from 5/10 spoligotype negative isolates. Conclusion and Recommendation: Although M. tuberculosis is the dominant AFB associated with chronic pulmonary disease in Jos, Nigeria, other clinically relevant mycobacteria were observed in the study. This suggests that other AFB positive microorganisms associated withtuberculosis -like symptoms could be misdiagnosed and incorrectly treated as M. tuberculosis. It is therefore necessary for laboratories in TB high burden countries to step up diagnostic procedures beyond routine smear microscopy.